An overview of the Botswana urban class structure and its articulation with the rural mode of production: Insights from Selebi-Phikwe - Cooper, David (My University, 1981)
This paper is adapted from the paper of similar title recently given at the "Symposium on Settlement in Botswana" in Gaborone. Here I attempted to summarise, in a short paper, some of the central findings and theoretical perspectives which have been elaborated on in a series of four Working Papers circulated under the auspices of the Botswana National Migration Study - (NMS) (Cooper 1979, a, b, c, 1980, henceforth WP1, 2, 3, 4). In these latter papers, the central themes tended to be submerged under a weight of empirical data and necessary qualifications/footnotes. It was thus felt that a summary paper was worthwhile, in order to generate a wider debate on issues concerning the Botswana urban-based classes and their interrelations with the rural class structure. Of course, what then possibly emerges from such a brief overview is a class structure too crudely drawn, and certain jupotheses which appear too unqualified. These problems inherent in the paper for the Symposium are equally applicable to this summary of the Working Papers here. In addition, such an overview takes, for instance, forms of land tenure in Botswana, the historical generation of the labour reserve economy, etc., as an accepted baseline with very little elaboration on this background. Nonetheless, it is felt desirable to focus this summary as much as possible on the issues of the class structure, and therefore of necessity to take such background coordinates as given. In this way, the discussion to follow this paner might more readily be able to centre on general problems of conceptualising the articulation of modes of production in post-colonial African states, and the accompanying class structures. If desired, some of this Botswana socio-economic 'background'can be gone into in this ensuing discussion. In summarising the central arguments in these four Working Papers, it must also be stressed that the fundamental external determinants of Botswana's internal class structure are largely ignored by these Papers. These include the economic role of USA and EEC capital through direct (e.g. mining) investment and more importantly, trading (e.g. cattle) linkages; the latters interrelationship with the enormous input of foreign personnel into the political realm of the Botswana state'; as well as the effects, primarily economic, of South African capital in its increasingly subordinate role vis-a-vis these other capitals since Independence. These are thus taken as additional 'givens' in this summary here of these Papers which focused on the internal dynamics of the Botswana social formation i.e. internal effects, which, though they have their own relative autonomy/ are dominated by this external dynamic.
African Studies Seminar series. Paper presented 2 June, 1981
Keywords: Working class. Botswana. Selebi-Pikwe; Botswana. Rural conditions; Urbanization. Botswana. Selebi-Pikwe